357 Gamma Knife Stereotactic Radiosurgery in the Management of Large Cerebral Arteriovenous Malformations. (1st August 2016) - Singh, Manmohan; Aggarwal, Deepak; Kale, Shashank Sharad
Abstract: INTRODUCTION: Large brain arteriovenous malformations (AVMs) pose management challenge in neurosurgical practice. Management remains conservative unless these AVMs bleed or present with neurological deficits. For patients who require treatment, options are limited with very high treatment-related morbidity. Gamma knife radiosurgery remains an excellent noninvasive option for such AVMs. METHODS: This is a retrospective study of 74 patients with large AVMs who were treated with gamma knife radiosurgery over 16 years. Sixty-five patients were treated with single-fraction and 9 patients were treated with volume-staged gamma knife radiosurgery. Average follow-up was 4.2 years. RESULTS: In the single-fraction group, 90% patients had SM grade 3 and 4 AVMs while 10% patients had SM grade 5 AVMs. Mean marginal radiation dose was 23.66 Gy. Overall obliteration rate of 66% was observed. Four percent of patients rebled in this group. Postradiation edema was observed in 18% of patient who presented with headache, new-onset seizures, and motor deficits. The symptoms improved with steroid therapy in most patients. Delayed cyst formations were seen in 2 patients. Interestingly, 41% patients showed seizure control after gamma knife radiosurgery. In volume-staging group, 60% patients had SM grade 4 AVMs and 40% patients has SM grade 5 AVMs. All patients were treated in 2 sittings. Average marginal dose used was 23 Gy. These patients showed nearly 80% reduction in the nidus volume at follow-up. No new-onset deficit was observed in this group, and all patients tolerated the treatment very well. CONCLUSION: Large-volume AVMs can be managed with gamma knife radiosurgery with acceptable risks. Single-fraction gamma knife radiosurgery should be considered for moderate-size AVMs away from critical structures. Large-volume lesions should be treated with volume-staged gamma knife radiosurgery.